Effects of principal leadership: teachers' involvement in reconstructing schools - Cholakian, Rima (Beirut Haigazian University - Faculty of Arts and Sciences - Department of Education, 2004)
To have a restructures school, an effective principal is needed. The list of the Armenian schools was taken from the Armenian Evangelical Educational Council, and a questionnaire was given to two hundred twenty-seven full-time teachers. A research was conducted using the Armenian private schools of Beirut to test the following hypotheses (If principals empower their teachers in decision-making processes, if teachers feel they are accountable to their principals, if teachers perceive their principals to be effective, if teachers have high values in themselves and each other, then restructuring can be implemented positively and effectively) pertaining to a number of factors related to restructuring. The questionnaire consisted of thirty-one questions. A stepwise multiple regression analysis was run to find the relationship between restructuring as perceived positively by teachers and all other factors affecting restructuring. The affected factors were empowerment of teachers in decision-making, accountability of teachers toward their principals, perception of the teachers toward their principals as being effective, and teachers having high values in themselves and each other. Teachers believe that the effective principal is the key and pivotal person to restructure the school. On the other hand, the principals should be aware of the teachers' opinions and they should not underestimate them because teachers are better able to spot areas of improvement, identify solutions and take corrective actions than the principals. To have a restructured school, effective principal and teachers should work hand-in-hand. This implies that principals' and teacher's attitude, students' learning and outcome will be affected positively.
: Mémoire
Keywords: Gestion scolaire; Les Attitudes et conceptions des enseignants; Reconstruction; Reconstruction; Teachers attitudes and conceptions School management